Digitalizing the College of Architecture Museum - Lopez, Karen Therese F. (2023)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/9529/8409
Keywords: Museum architecture; Virtual museums; University of the Philippines (Diliman). College of Architecture